Squamous Cell Rectal Carcinoma: About A Rare and Unusual Case: A Case report - Bouatmani, M. El; Michouar, M.; Jallouli, A.; Errami, A. Ait; Oubaha, S.; Samlani, Z.; Krati, K.; Rachidi, H.; Belbachir, A. (International Journal of Innovative Research in Medical Science, 2021)
Primary squamous cell rectal carcinoma is a rare malignancy that accounts for 0.3% of rectal tumors. To this date, no sure risk factors have been determined. The etiopathogeny is still unknown, despite the different suggested hypotheses. Specific diagnosis criteria have been set, to identify rectal squamous cell carcinoma from another entity. Moreover, due to its rarity, only few data exist on its management, and no standardized therapeutic regimen was set. We report a very rare case of primary squamous cell rectal carcinoma found in the middle rectum, in a 73-year-old woman. Rectos copy was used to visualize the tumor mass and to take biopsies; their histological study revealed a rectal location of a squamous cell carcinoma. After discussion of the case in a multidisciplinary consultation meeting, management consisted of definitive chemo-radiation.